GENDER PERFORMANCE DISCOURSE ON TINDER PROFILE PICTURES IN LONDON, UK – A SOCIAL SEMIOTICS STUDY - Dery Rovino; Michael Jibrael Rorong; Jai Kishon Goswami (Bricolage : Jurnal Magister Ilmu Komunikasi, 2020)
ABSTRACT Cyclical and bidirectional relationship(s) between technology and today’s romantic gratifications have reformed how people seek romance. On another end, gender performances largely underpin humans’ romantic gratification. This is where Tinder, as a dating application, affords unique opportunities for those seeking romances through portraying gender performances. A number of studies concluded that, in romance-seeking ventures, male’s masculinity and female’s femininity generally remained conformist to their respective biological attributes. Therefore, this study aimed to evaluate nuances of gender performances portrayed in dating apps such as Tinder. Since Tinder profile picture, as a form of visual text, is a source rife with gender performance cues, this study focused on the visual component – profile pictures. Profile Picture Protocol (PPP), derived from notable social semiotics frameworks, was established. This study revealed that, albeit a major affinity towards more saturated bright colors in the observed data, color choices in profile pictures were not conclusive to determine gender performatives, mainly due to possible duality in meanings when other elements (body gestures and clothing choices) were taken into consideration. Formal clothing choices were only found in the male group, which was conformist to the previous studies. Foregrounding bodily features was evident in both male and female group’s profile pictures, which indicated that the male group also exuded an element of femininity, which leaned towards contestating the previous findings. Actors’ angles that were frontal as well as eye-level, indicated a need for social closeness and friendliness emulation, were fashionable in both gender groups, which was initially prevalent in the female group. Limitations were put forth. Keywords; profile picture; visual text, social semiotics, gender performance, Tinder ABSTRAK Hubungan siklus dan dua arah antara teknologi dan gratifikasi romantisme dewasa ini telah mengubah cara orang mencari hubungan romansa. Di sisi lain, ekspresi gender umumnya mendukung gratifikasi romantis manusia. Di sinilah Tinder, sebagai aplikasi kencan, memberikan peluang unik bagi mereka yang mencari romansa melalui ekspresi gender. Sejumlah penelitian menyimpulkan bahwa, dalam usaha pencarian romansa, maskulinitas pria dan femininitas wanita umumnya tetap mengikuti atribut biologis masing-masing. Oleh karena itu, penelitian ini bertujuan untuk mengevaluasi ekspresi gender yang digambarkan dalam aplikasi kencan seperti Tinder. Karena gambar profil Tinder, sebagai bentuk teks visual, adalah sumber penuh dengan isyarat ekspresi gender, penelitian ini berfokus pada komponen visual - gambar profil. Profile Picture Protocol (PPP), berasal dari kerangka kerja semiotika sosial terkemuka, dikonstruksikan. Studi ini mengungkap bahwa, meskipun memiliki ketertarikan umum terhadap warna-warna cerah yang lebih jenuh pada data yang diamati, pilihan warna dalam gambar profil tidak konklusif untuk menentukan ekspkresi gender, terutama karena kemungkinan dualitas dalam makna ketika elemen lain (gerakan tubuh dan pilihan pakaian) disertakan dalam pertimbangan. Pilihan pakaian formal hanya ditemukan pada kelompok pria, yang sesuai dengan penelitian sebelumnya. Gambaran tubuh terdepan terlihat dalam gambar profil kelompok laki-laki dan perempuan, yang menunjukkan bahwa kelompok laki-laki juga memancarkan unsur feminitas, yang condong ke arah mengontestasi temuan sebelumnya. Sudut para aktor yang frontal maupun setinggi mata, mengindikasikan keinginan atas kedekatan sosial dan emulasi keramahan, yang umum di kedua kelompok gender, yang awalnya lazim di kelompok perempuan. Keterbatasan penelitian disampaikan. Kata Kunci; teks visual, Semiotika Sosial, performa gender, aplikasi berkencan.